1994
DOI: 10.1038/bjc.1994.182
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of the accumulation of p53 tumour-suppressor gene protein in gastric adenocarcinoma

Abstract: SummaryWe have studied the expression of p53 in 206 patients with gastric adenocarcinomas. A standard immunohistochemical technique employing the CM-1 anti-p53 polyclonal antibody was applied to the routinely fixed and paraffin-embedded material from these tumours; overexpression of p53 was defined as positive nuclear staining: 46% (94/206) of gastric carcinomas expressed high levels of p53. There was no significant correlation between p53 positivity and the tumour grade, growth pattern, the Lauren type or lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 35 publications
6
39
0
1
Order By: Relevance
“…Other investigators have also shown that p21 loss correlates positively with the depth of cancer invasion and also stage progression in primary prostate cancer (Gao et al, 1995). Similar abnormalities have been reported in studies of other cell cycle-regulating factors such as p53 (Joypaul et al, 1994), Rb (Constancia et al, 1994), cyclins (Tahara E, 1994) and PCNA (Maeda et al, 1994). Our study and others suggest that cell cycle deregulation is an important factor in gastric cancer progression.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Other investigators have also shown that p21 loss correlates positively with the depth of cancer invasion and also stage progression in primary prostate cancer (Gao et al, 1995). Similar abnormalities have been reported in studies of other cell cycle-regulating factors such as p53 (Joypaul et al, 1994), Rb (Constancia et al, 1994), cyclins (Tahara E, 1994) and PCNA (Maeda et al, 1994). Our study and others suggest that cell cycle deregulation is an important factor in gastric cancer progression.…”
Section: Resultssupporting
confidence: 90%
“…Thus, it is reasonable to investigate the involvement of p53 function in cell cycle regulation by examining p21 protein expression. The p53 gene is an important tumour suppressor, and the correlation between its overexpression and tumour progression has been shown in gastric carcinoma (Martin et al, 1992;Joypaul et al, 1994;Gabbert et al, 1995 Cancer, 1981) were used for the clinicopathological classification, with one exception: tumours were divided into two histological subgroups -a differentiated type, which consisted of papillary and tubular adenocarcinomas, and an undifferentiated type, which included poorly differentiated adenocarcinoma, signet ring cell carcinoma and mucinous adenocarcinoma. All patients underwent gastrectomy.…”
mentioning
confidence: 99%
“…p53 expression was detected in 46% of patients, which falls within the range (40 -60%) of previously published gastric cancer series (Joypaul et al, 1994;Gabbert et al, 1995;Victorzon et al, 1996). Use of the immunohistochemical detection of p53 as a prognostic marker has yielded conflicting results (Fenoglio-Preiser et al, 2003).…”
Section: Discussionsupporting
confidence: 50%
“…The loss of p53 function is related to the progression of the tumor by allowing cells with damaged DNA to continue to multiply (23). In some studies, p53 expression in stomach cancer has been reported to be bad prognosis (9)(10)(11)(12)(13)(14), but other reports have shown that p53 expression has no effect on clinical results (24)(25)(26). The reasons for these conflicting results are unclear.…”
Section: Discussion Discussionmentioning
confidence: 43%
“…Mutation in the p53 gene is one of the most common genetic lesions associated with gastric cancer, and some studies have reported that the expression of p 53 is related to bad prognosis (9)(10)(11)(12)(13)(14).…”
Section: Introduction Introductionmentioning
confidence: 99%